Effectiveness of Registration Standards in the Classification of Inmates - Wilson Santoso Tambun; Rahul Ardian Fikri; Hasdiana Juwita Bintang (CERED Indonesia Institute, 2025)
The registration and classification of inmates constitute a fundamental initial stage in the administration of the correctional system, as they form the basis for placement decisions, security management, and individualized rehabilitation programs. Registration standards, as regulated through technical guidelines and administrative instruments within correctional units, are intended to ensure accurate data recording, risk identification, and the formulation of effective treatment and development programs. However, their implementation continues to face various challenges that affect the overall effectiveness of inmate classification. Empirical studies conducted across several correctional institutions indicate that limitations in human resources, infrastructure constraints, and insufficient training of assessment officers hinder the consistent application of registration standards in accordance with established guidelines. As a result, the objective of achieving appropriate inmate grouping and the optimal design of individualized correctional programs has not been uniformly realized. At the normative level, the enactment of Law Number 22 of 2022 concerning Corrections has renewed the legal framework previously governed by Law Number 12 of 1995. The new statute reinforces the principles of individualization, continuity, and the protection of inmates’ rights as integral components of a modern correctional system oriented toward rehabilitation and social reintegration. Although this updated legal framework strengthens the rights-based and evidence-based orientation of correctional administration, the technical regulation of registration and classification procedures remains largely dependent on guidelines issued by the Directorate General of Corrections. Consequently, further harmonization between statutory provisions and technical instruments is necessary to enhance legal certainty and operational effectiveness. These findings demonstrate that the effectiveness of registration standards in inmate classification is determined not solely by the quality of written regulations, but also by institutional capacity, administrative coherence, and the availability of adequate resources to ensure accurate and sustainable implementation.